TURNAROUND STRATEGY FOR STAGNANT MARKET CONDITION ON FITNESS BUSINESS IN SOUTH JAKARTA INDONESIA - Joseph M. J. Renwarin (Jurnal Inovasi Penelitian, 2021)
This research is case study on how the turnaround strategy to growth strategy. The phenomenon is stagnant to declining condition on fitness business in Jakarta city. The objective of research is evaluate the condition of stagnant market of membership Fitness business in South Jakarta Indonesia. The method of this research is the Cause-effect examines the correlation and effect between two or more variables. The author carries out the research by using quantitative descriptive approach with cause-effect method using simple and multiple regression. The author finds that there are correlations and effects of independent variables such as product, price, location, promotion, people, process and physical evidence to customer loyalty. The result of this research shows that marketing mix variable such as product, price, place, promotion, people, process and physical evidence partially have significant effect to customer loyalty. The author find that managing people is very important as the front liner and as the main of the strategy.